Using 81Kr and noble gases to characterize and date groundwater and brines in the Baltic Artesian Basin on the one-million-year timescale. (15th May 2017) - Gerber, Christoph; Vaikmäe, Rein; Aeschbach, Werner; Babre, Alise; Jiang, Wei; Leuenberger, Markus; Lu, Zheng-Tian; Mokrik, Robert; Müller, Peter; Raidla, Valle; Saks, Tomas; Waber, H. Niklaus; et al.
Abstract: Analyses for 81 Kr and noble gases on groundwater from the deepest aquifer system of the Baltic Artesian Basin (BAB) were performed to determine groundwater ages and uncover the flow dynamics of the system on a timescale of several hundred thousand years. We find that the system is controlled by mixing of three distinct water masses: Interglacial or recent meteoric water (δ 18 O ≈ −10.4‰) with a poorly evolved chemical and noble gas signature, glacial meltwater (δ 18 O ⩽ −18‰) with elevated noble gas concentrations, and an old, high-salinity brine component (δ 18 O ⩾ −4.5‰, ⩾ 90 g Cl − /L) with strongly depleted atmospheric noble gas concentrations. The 81 Kr measurements are interpreted within this mixing framework to estimate the age of the end-members. Deconvoluted 81 Kr ages range from 300 ka to 1.3 Ma for interglacial or recent meteoric water and glacial meltwater. For the brine component, ages exceed the dating range of the ATTA-3 instrument of 1.3 Ma. The radiogenic noble gas components 4 He ∗ and 40 Ar ∗ are less conclusive but also support an age of > 1 Ma for the brine. Based on the chemical and noble gas concentrations and the dating results, we conclude that the brine originates from evaporated seawater that has been modified by later water–rock interaction. As the obtained tracer ages cover several glacial cycles, we discuss the impact of the glacial cycles on flow patterns in the studied aquifer system.